Implementasi Kurikulum Pendidikan Pada Program Studi Lalu Lintas Udara di Politeknik Penerbangan Makassar (Studi Evaluasi Materi Aerodrome Control Procedures) - Idyaningsih, Nining; Rusman; Supardam, Dhian (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2021)
Higher education as a form of education unit that provides academic and or professional knowledge must be able to provide services and produce quality outputs through strategic programs. Graduates are expected to be able to overcome the problems above. Many factors can affect the quality of higher education such as lecturers, infrastructure, curriculum and teaching and learning processes, as well as the assessment system. Likewise, the parameters of the quality of education, both in terms of input, process, product, and outcome always change from time to time. The purpose of this study is to find out what inputs, transformations, outputs and outcomes are from the results of implementing the curriculum in the Air Traffic Management study program. The method of collecting data is through interviews in the form of direct questions and answers to informants representing alumni and lecturers and with observations which are then followed by data analysis so that the data will be more focused on predetermined problems. The technique used in analyzing for this research is descriptive qualitative.